The Heritage of Edirne in Ottoman and Turkish Times Continuities, Disruptions and Reconnections - Krawietz, Birgit; Riedler, Florian (Studies in the history and culture of the Middle East ;, 2020)
Modern scholarship has not given Edirne the attention it deserves regarding its significance as one of the capitals of the Ottoman Empire. This edited volume offers a reinterpretation of Edirne's history from Early Ottoman times to recent periods of the Turkish Republic. Presently, disconnections and discontinuities introduced by the transition from empire to nation state still characterize the image of the city and the historiography about it. In contrast, this volume examines how the city engages in the forming, deflecting and creative appropriation of its heritage, a process that has turned Edirne into a UNESCO heritage hotspot. A closer historical analysis demonstrates the dissonances and contradictions that these different interpretations and uses of heritage produce. From the beginning, Edirne was shaped by its connectivity and relationality to other places, above all to Istanbul. This perspective is employed at many different levels, e.g., with regard to its population, institutions, architecture, infrastructures and popular culture, but also regarding the imaginations Edirne triggered. In sum, this multi-disciplinary volume boosts urban history beyond Istanbul and offers new insight into Ottoman and Turkish connectivities from the vantage point of certain key moments of Edirne's history.